Penguatan Karakter Pancasila melalui Keteladanan Guru Pendidikan Kewarganegaraan - Fitriya Wulansari; Encep Syarief Nurdin; Yadi Ruyadi (Pancasila: Jurnal Keindonesiaan, 2025)
Character building as an effort to fulfil Pancasila as mandated in the opening of the 1945 Constitution is a guideline for educators to provide role models in accordance with Pancasila values ​​for students and the younger generation. This study aims to determine the factors that cause the lack of practice of Pancasila values ​​in students, and to determine the Role of Teachers and Role Models through daily behavior. The research method used is a descriptive qualitative method with a literature study approach. Data were obtained from literature review of Education journals. The results of this study explained that the factors causing the lack of practice of Pancasila values ​​in students are the Lack of Practice of Pancasila Values, the Role of Teachers and Parents, the Pancasila Student Program, the Influence of the Social Environment, the Challenges of Media and Technology so that efforts to improve understanding and practice of Pancasila values ​​require cooperation from all parties, to form a young generation with character and morals in accordance with the ideology of the Indonesian nation. Then for the Role of Role Models in building Pancasila character to Students including. The Role of Teachers and Role Models through daily behavior, such as showing tolerance, respecting diversity, and teaching cooperation. Learning Environment and Practical Activities such as mutual cooperation and social activities can strengthen their understanding of Pancasila values ​​and foster important life skills. Positive Reinforcement and Motivation by implementing Pancasila values ​​in education, deviant behavior can be minimized, and students are expected to become nationalistic and patriotic individuals. The Importance of Families in providing good guidance and role models for children, so that children can grow into obedient, caring, and well-mannered individuals.